L1 as a Semiotic Tool: Deconstructing Grammatical Scaffolding in a Low-Exposure EFL Context in Indonesia - Feisal Aziez; Novan Andrianto; Arifin Muslim; Aleeyah Masae; John Louie Domingo Galang (Language, Technology, and Social Media, 2026)
The instruction of abstract grammatical concepts, such as the Present Continuous Tense, presents significant cognitive challenges for Young Learners in English as a Foreign Language (EFL) context, particularly where exposure to the target language is limited. While traditional "English-Only" pedagogies often view the use of the First Language (L1) as a hindrance, recent "multilingual turn" perspectives argue for its value as a cognitive resource. This study investigates the pedagogical functions of L1 (Indonesian) in a Grade 4 EFL classroom at a public elementary school located in the Sumenep region, East Java, Indonesia. Employing a descriptive qualitative case study design, the research utilizes Classroom Discourse Analysis (CDA) to examine the verbal interaction of a teacher candidate during a 73-minute instructional session. Preliminary analysis revealed that the teacher utilized L1 for approximately 80% of the instruction. However, rather than indicating a lack of proficiency, micro-analysis of the discourse demonstrates that this code-switching served as a systematic scaffolding strategy. The findings reveal four primary pedagogical functions of L1: (1) Meta-linguistic Scaffolding, used to bridge the conceptual gap between Indonesian lexical time markers and English morphological inflection; (2) Interactive Scaffolding, employed to repair communication breakdowns and sustain the Initiation-Response-Feedback (IRF) cycle; (3) Managerial Scaffolding, utilized to reduce extraneous cognitive load during complex task instructions; and (4) Affective Scaffolding, used to build rapport and reduce anxiety. The study concludes that in low-exposure TEYL contexts, the L1 functions not as a barrier, but as a vital semiotic tool that transforms abstract linguistic input into comprehensible intake.